Zastosowanie lasera CO2 podczas zabiegu chirurgicznego usunięcia naczyniaka jamistego wargi dolnej u 78-letniej pacjentki = The use of CO2 laser during surgery to remove hemangioma lower lip at the 78-year-old patient - Szczepkowska, Aleksandra; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2016)
Szczepkowska Aleksandra, Osica Piotr, Janas-Naze Anna. Zastosowanie lasera CO2 podczas zabiegu chirurgicznego usunięcia naczyniaka jamistego wargi dolnej u 78-letniej pacjentki = The use of CO2 laser during surgery to remove hemangioma lower lip at the 78-year-old patient. Journal of Education, Health and Sport. 2016;6(3):97-105. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47725 http://ojs.ukw.edu.pl/index.php/johs/article/view/3426 https://pbn.nauka.gov.pl/works/720683 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016. Zastosowanie lasera CO2 podczas zabiegu chirurgicznego usunięcia naczyniaka jamistego wargi dolnej u 78-letniej pacjentki The use of CO2 laser during surgery to remove hemangioma lower lip at the 78-year-old patient Aleksandra Szczepkowska, Piotr Osica, Anna Janas-Naze Zakład Chirurgii Stomatologicznej UM w Łodzi Kierownik: dr hab. n. med. prof. nadzw. Anna Janas-Naze Adres do korespondencji: Aleksandra Szczepkowska Zakład Chirurgii Stomatologicznej UM w Łodzi 92-213 Łódź, ul. Pomorska 251 e-mail: aleksandra.szczepkowska@gmail.com tel. 42 675 75 71 Praca finansowana przez Uniwersytet Medyczny w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001 Streszczenie: W pracy przedstawiono przypadek zastosowania lasera CO2 do wykonania zabiegu usunięcia naczyniaka jamistego wargi dolnej u 78-letniej pacjentki. Słowa kluczowe: naczyniak jamisty, laser CO2. Summary: The article describes a case of hemangioma, methods of diagnostic and treatment. Key words: hemangioma, CO2-laser.